Analisis Implementasi Program Pemberdayaan Komunitas Adat Terpencil (KAT) di Kelurahan Selensen Kabupaten Indragiri Hilir - Anisa, Anisa; Dewi, Ratna (PUBLICNESS: Journal of Public Administration Studies, 2024)
This study aims to analyze the implementation of the Remote Indigenous Community (KAT) empowerment program in Selensen Village, Kemuning District, Indragiri Hilir Regency. This program is a government initiative explicitly aimed at the KAT community. This research uses a descriptive method with a qualitative approach, where data is collected through observation, interviews, and documentation. Research informants were determined using a purposive sampling technique, and data were analyzed using qualitative analysis. The results showed that the implementation of the KAT empowerment program in Selensen Village was successful but can only be partially successful. Of the six indicators analyzed, namely policy standards and objectives, human resources, inter-organizational communication, institutional characteristics, social, economic, and political conditions, and implementor disposition, only two indicators, inter-organizational communication and institutional factors, meet the criteria for effective implementation.